Fish, Mogi Guacu reservoir and four oxbow lakes, state of São Paulo, Brazil. - Goncalves, Cristina da Silva; Braga, Francisco Manoel de Souza [UNESP] (My University, 2010)
The Mogi Guacu River is one of the largest rivers in state of São Paulo, belonging to Parana hydrographic system. A study about fish composition in the Mogi Guacu reservoir and four oxbow lakes downstream the reservoir is showed. A total of 2,367 individuals from six orders, 17 families, and 46 species were collected during August 2005 to July 2006, using gillnets, traps and hand nets. In the reservoir were found 31 species and in the oxbow lakes 24, in which Curimatidae and Characidae were the most abundant families, respectively.